(untitled) (Nexus International Journal of Science and Education, 2024)
The study assessed the relationship between School Heads’ Professional Socialization and its association with Teachers’ Leadership Development in Gov. Generoso South District, Davao Oriental Schools Division. The study used a non-experimental descriptive-correlational research design, utilizing an adapted survey instrument to gather responses from the randomly selected 120 teacher respondents. Data gathered were treated using Mean scores with descriptive interpretation, Pearson r, and Simple Linear Regression Analysis. Findings revealed that of school head’s professional socialization exhibits continuous learning growth; collaborative decision-making, vision-mission alignment and ethical leadership are moderately extensive, while mentorship and coaching are extensive, while, the extent of teacher’s leadership development shows that innovative teaching practices, participation in decision-making and professional development advocate are extensive, while reflective practice is moderately extensive. There is a significant relationship between the school head’s professional socialization and the teacher’s leadership development. All domains of the school head’s professional socialization in terms of continuous learning and growth, mentorship and coaching, collaborative decision-making, ethical leadership, and vision and mission alignment significantly influenced teachers’ leadership development. Future research may explore the long-term impact of teacher leadership on student outcomes and school performance, which would contribute valuable insights.